TRANSAKSI AFILIASI DAN KEPUTUSAN PENGENDALI AKHIR: PRAKTIK MANAJEMEN LABA - Malawat, Fadli Fendi; Pelupessy, Fatmah Watty; Yaman, Afdhal; Relubun, Dety Aryani; Nacikit, Muhammad Reza (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This paper aims to explore the relationship between affiliate transactions and earnings management practices, focusing on the moderating role of ultimate controlling ownership. Using data from manufacturing companies from 2019 to 2021, the research employs moderated regression analysis to examine these dynamics. The findings reveal a positive relationship between affiliate transactions and earnings management practices in the short term. However, in the long term, dominant ultimate controlling ownership drives affiliate transaction policies and earnings management practices toward more opportunistic behavior. This study acknowledges certain limitations, particularly excluding other dimensions, such as socioemotional aspects and organizational culture, which may influence the relationships between variables. Consequently, future research is encouraged to expand the analysis to incorporate these dimensions, potentially assessed subjectively through surveys, to provide a deeper understanding of the influence of family business heterogeneity on earnings management practices. Furthermore, this study offers practical contributions by proposing mechanisms to mitigate the risks of opportunistic behavior in earnings management practices. These mechanisms can be achieved by implementing more inclusive corporate governance, such as involving independent parties in strategic decision-making processes.